Investigating Transit Timing Variations in the Ultrashort Period Exoplanet WASP-19b - Shraddha Biswas; Ing-Guey Jiang; Li-Chin Yeh; Hsin-Min Liu; Kaviya Parthasarathy; Devesh P. Sariya; D. Bisht; Mohit Singh Bisht; A. Raj (The Astronomical Journal, 2025)
In this study, we present a comprehensive analysis of transit timing variations (TTVs) in the ultrashort-period gas giant WASP-19b, which orbits a G-type main-sequence star. Our analysis is based on a data set comprising 204 transit light curves (LCs) obtained from the Transiting Exoplanet Survey Satellite, the Exoplanet Transit Database, and the ExoClock project, supplemented by 18 publicly available LCs. Mid-transit times were extracted from these data, and an additional 98 mid-transit times compiled from the literature were incorporated, resulting in a combined data set spanning 14 yr. After excluding LCs significantly impacted by stellar activity, such as starspot anomalies, the final data set consisted of 252 high-quality mid-transit times. Initial inspection of the transit timing residuals using an apsidal precession model suggested the possible presence of an additional planetary companion. However, subsequent frequency analysis and sinusoidal model fitting indicate that the observed TTVs are more consistently explained by apsidal precession of WASP-19b’s orbit. We also considered alternative mechanisms, including the Applegate mechanism and the Shklovskii effect. Our findings suggest that stellar magnetic activity, potentially linked to the Applegate mechanism, may also contribute to the observed timing variations. To further constrain the origin of the TTVs and assess the contributions of these mechanisms, continued high-precision photometric monitoring of the WASP-19 system is strongly recommended.